The Tuscany Masonry Database Website - Sonia Boschi; Chiara Bernardini; Andrea Vignoli (Heritage, 2021)
The Tuscany Masonry Database (TMDB) is an online database containing the results and the complete experimental data of in situ experimental tests carried out on masonry panels of masonry buildings located in the Tuscany Region (Italy), starting from 1990. The results can be freely downloaded by users after registration on the site. To date, the TMDB includes 142 georeferenced tests, comprising 50 diagonal tests, 5 compression tests, and 87 flat-jack tests. In addition, there are tests on the components, such as compression tests on blocks, penetrometric testing on mortar, macroscopic or microscopic analysis of mortar, and coring. The results are supported by a qualitative description of the masonry texture and are compared with the reference values of the mechanical characteristics proposed by the Italian Building Code. The data come from scientific literature and are the result of collaborations between the Seismic Sector of the Tuscany Region and some Tuscan University Laboratories, or they are shared by private test laboratories mainly acting in Tuscany. The TMDB was developed and is constantly updated by the authors to provide support to researchers and freelance engineers in the knowledge process phase of masonry buildings, as well as for that of particular structures, such as heritage buildings. Furthermore, it allows for the filling of the lack of particularity of masonry classification and for the consideration of particular masonry types existing in local areas, for which there are no literature data or specific experimentation. Further tests are currently being processed to be included in the database, and divulgation activity on the project is foreseen. Furthermore, national and international collaborations are underway for the expansion of the database, with the aim of unifying test procedures and updating the codes.